2020
DOI: 10.1038/s41598-020-75389-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in type of exercise associated with depression in South Korean adults

Abstract: Exercise has been considered as treatment and a preventive modality to alleviate depressive symptoms, but sex differences regarding specific types of exercise in association with depression have not been clearly elucidated. Here, we investigated sex differences in the association between exercise type and depression in Korean adults. Data from the Korea National Health and Nutrition Examination Survey (KNHANES) were used for this study. A total of 13,914 participants who had filled in a Patient Health Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The data used in this study were obtained from the 2015–2019 Korea National Health and Nutrition Examination Survey (KNHANES), a cross-sectional and nationwide survey conducted by the Korea Disease Control and Prevention Agency. The KNHANES was designed to evaluate the health status, health behavior, and nutritional status of the South Korean population to provide basic data for developing nationwide health policies [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data used in this study were obtained from the 2015–2019 Korea National Health and Nutrition Examination Survey (KNHANES), a cross-sectional and nationwide survey conducted by the Korea Disease Control and Prevention Agency. The KNHANES was designed to evaluate the health status, health behavior, and nutritional status of the South Korean population to provide basic data for developing nationwide health policies [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Informed consent was obtained from all respondents in advance and all data analyzed in this study were fully anonymized. As the KNHANES complies with the Declaration of Helsinki and provides publicly accessible data, further ethical approval for the use of these data was not required [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Each question is rated as 0 (“not at all”), 1 (“for many days”), 2 (“for more than a week”), and 3 (“almost daily”), resulting in a maximum score of 27 points [ 18 ]. It has been proven to be a reliable tool not only for screening individuals with depression but also for evaluating the severity of the illness [ 19 ]. Individuals were considered to show depressive symptoms if they scored > 10 points on this questionnaire [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…A previous study reported that men were more likely to develop hypertension than women among young adults [43,44]. Furthermore, it was documented that sex affected motivation toward physical exercise and modified the association of physical exercises with health outcomes [45,46]. On the other hand, compared to men, women were more likely to consume vegetables but less likely to consume soft drinks [47].…”
Section: Discussionmentioning
confidence: 99%